2020
DOI: 10.14302/issn.2471-2140.jaa-20-3478
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Surinamese Medicinal Plants with Adaptogenic Properties and Correlation with Total Phenolic Contents

Abstract: Plant-based preparations are commonly used in Suriname (South America) as adaptogens. In this study, fifteen alleged adaptogenic Surinamese plants have been assessed for their antioxidant activity (AA), total phenolic contents (TPC), and total flavonoid contents (TFC). The investigated plants were Anacardium occidentale, Spondiasdulcis, Annona muricata, Euterpe oleracea, Oenocarpus bacaba, Luffa acutangula, Punicagranatum, Malpighia emarginata, Syzygiumaqueum, Syzygiumcumini, Averrhoa carambola, and Renealmiaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The reasons that the pro-angiogenic or anti-angiogenic effects of the M. citrifolia, L. acutangula, M. charantia, and P. guajava samples did not manifest in the current study might also be attributed to differences in one or more of the experimental conditions applied [40]. Alternatively, the wound healing-stimulatory effects of these plants may be due to mechanisms other than those related to angiogenesis such as the promotion of inflammation and maturation/remodeling.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The reasons that the pro-angiogenic or anti-angiogenic effects of the M. citrifolia, L. acutangula, M. charantia, and P. guajava samples did not manifest in the current study might also be attributed to differences in one or more of the experimental conditions applied [40]. Alternatively, the wound healing-stimulatory effects of these plants may be due to mechanisms other than those related to angiogenesis such as the promotion of inflammation and maturation/remodeling.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, these polyphenolic compounds have been identified at relatively high concentrations in fruit, leaf, and root of O. bacaba and the closely related O. bataua Mart. and displayed appreciable antioxidant activity [34,[38][39][40] which might be involved in their wound healing-stimulatory activities [39]. However, it must be taken into account that several studies have also associated the polyphenolic compounds with anti-angiogenic instead of pro-angiogenic effects [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators also reported that M. glabra fruit extracts displayed a relatively high total phenolic content and in vitro antioxidant activity which correlated well with each other [114,125,[128][129][130]. Thus, the remarkable antioxidant activity of M. glabra fruit is most probably not only attributable to its relatively high content of vitamin C but also to phenolic phytonutrients with antioxidant activity which may act synergistically with vitamin C [123].…”
Section: Antioxidant Vitamins: Vitamin C: Malpighia Glabra L (Malpigh...mentioning
confidence: 80%
“…The beneficial health effects of M. glabra fruit have been associated with its powerful antioxidant effects in several in vitro assays [119][120][121] which, in their turn, have been attributed to its abundant amount of vitamin C as well as phenolic compounds (including benzoic acid derivatives, phenylpropanoid derivatives, flavonoids, and anthocyanins) and carotenoids [114,[122][123][124][125]. Notably, the vitamin C content of M. glabra fruit is 1000-4500 mg per 100 g, which is 50-100 times that of an orange or a lemon [125]. When considering that the recommended dietary allowances of vitamin C are 75 mg/day for women and 90 mg/day for men [126], the consumption of three M. glabra fruits per day would satisfy the required daily vitamin C intake for an adult [127].…”
Section: Antioxidant Vitamins: Vitamin C: Malpighia Glabra L (Malpigh...mentioning
confidence: 99%
“…Several of the plant species mentioned in the preceding paragraph are renowned for their high nutritious content and are regarded as nutraceuticals, functional food ingredients, or adaptogens [35, [66][67][68] and/or used as traditional medicines [69][70][71][72][73][74][75][76][77][78]. In some cases, these qualifications are attributable to an exceptionally high content of phytochemicals with antioxidant activity, including phenolic compounds such as flavonoids, lignans, and coumarins; vitamins such as (pro)vitamins A, C, and E; and trace elements such as selenium.…”
Section: Naturally Occurring Antioxidants In a Few Well-known Surinam...mentioning
confidence: 99%